Spatiotemporal differential regulation of extrasynaptic GluN2B receptor subunits and PSA-NCAM in brain aging and Alzheimer’s disease - Imiruaye, Oghenetega E.; Perez, Isis G.; Carson, Brian C.; Crouzet, Christian; Garcia, Jerome; Han, Derick; Bhattacharya, Subhrajit (Frontiers in Neuroscience, 2025)
IntroductionExtrasynaptic GluN2B N-methyl-D-aspartate receptors (ES-GluN2B) are localized outside synapses and promote excitotoxic signaling, apoptosis, and long-term depression (LTD) in Alzheimer’s disease (AD). Polysialylated neural cell adhesion molecule (PSA-NCAM) physiologically inhibits ES-GluN2B activity, and its downregulation is associated with impaired synaptic plasticity. However, the spatiotemporal changes of ES-GluN2B and PSA-NCAM during brain aging versus AD remain poorly understood.MethodsWe investigated GluN2A, GluN2B, ES-GluN2B, and PSA-NCAM expression across brain regions in young and old Tg2576 AD and wild-type (WT) mice. Additional experiments included PSD-95 pulldown assays, analysis of GluN2B phosphorylation at Ser1480, CRISPRa-driven ST8Sia4 upregulation in IMR-32 neuroblastoma cells, and Aβ treatment to assess effects on PSA-NCAM biosynthetic enzymes.ResultsNormal aging was associated with decreased GluN2B, increased GluN2A, stable ES-GluN2B, and elevated PSA-NCAM levels. In contrast, AD aging showed elevated ES-GluN2B and reduced PSA-NCAM, particularly in the hippocampus and cortex, with no change in total NCAM expression. PSD-95 pulldown revealed increased extrasynaptic GluN2B in aged AD brains. AD aging was associated with elevated phosphorylation of GluN2B at Ser1480 by casein kinase 2 (CK2), promoting GluN2B redistribution to extrasynaptic sites. CRISPRa-driven ST8Sia4 upregulation increased PSA-NCAM and reduced pGluN2B expression supporting a direct regulatory role for PSA-NCAM in GluN2B trafficking. Additionally, Aβ suppressed PSA-NCAM biosynthetic enzymes ST8Sia4 and UDP-E linking Aβ to impaired polysialylation.DiscussionThese findings highlight distinct regulatory patterns of ES-GluN2B and PSA-NCAM in AD versus normal aging and support a model in which impaired PSA-NCAM buffering facilitates pathological ES-GluN2B signaling and plasticity loss in AD progression.